The Successful Practice of Chinese-Chinese Female Legislators in Post-New Order Indonesia - Widjaya, Adeline Ilissa; Perdana, Phil. Aditya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
May 1998. According to Walujono, Suharto's rule, which led to the economic crisis in Indonesia during the New Order era, led the public to scapegoat ethnic Chinese as the perpetrators of the crisis.Their shops were robbed, looted, burned, and many ethnic Chinese women were raped and murdered.The representation of victims' identities in the media emphasized the characteristics of young, non-Muslim, non-indigenous, Chinese, and wealthy women.Hikmawati added that the rape was aimed at destroying the